(5+w)(5w+6)=0

Simple and best practice solution for (5+w)(5w+6)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (5+w)(5w+6)=0 equation:


Simplifying
(5 + w)(5w + 6) = 0

Reorder the terms:
(5 + w)(6 + 5w) = 0

Multiply (5 + w) * (6 + 5w)
(5(6 + 5w) + w(6 + 5w)) = 0
((6 * 5 + 5w * 5) + w(6 + 5w)) = 0
((30 + 25w) + w(6 + 5w)) = 0
(30 + 25w + (6 * w + 5w * w)) = 0
(30 + 25w + (6w + 5w2)) = 0

Combine like terms: 25w + 6w = 31w
(30 + 31w + 5w2) = 0

Solving
30 + 31w + 5w2 = 0

Solving for variable 'w'.

Factor a trinomial.
(5 + w)(6 + 5w) = 0

Subproblem 1

Set the factor '(5 + w)' equal to zero and attempt to solve: Simplifying 5 + w = 0 Solving 5 + w = 0 Move all terms containing w to the left, all other terms to the right. Add '-5' to each side of the equation. 5 + -5 + w = 0 + -5 Combine like terms: 5 + -5 = 0 0 + w = 0 + -5 w = 0 + -5 Combine like terms: 0 + -5 = -5 w = -5 Simplifying w = -5

Subproblem 2

Set the factor '(6 + 5w)' equal to zero and attempt to solve: Simplifying 6 + 5w = 0 Solving 6 + 5w = 0 Move all terms containing w to the left, all other terms to the right. Add '-6' to each side of the equation. 6 + -6 + 5w = 0 + -6 Combine like terms: 6 + -6 = 0 0 + 5w = 0 + -6 5w = 0 + -6 Combine like terms: 0 + -6 = -6 5w = -6 Divide each side by '5'. w = -1.2 Simplifying w = -1.2

Solution

w = {-5, -1.2}

See similar equations:

| 2(w+7)=1-(4+3w) | | Ln(x+4)=ln(7) | | 9y=6x-102 | | 27x^3-20x^2-96x-28=0 | | 27x^3-20x^2-96x+28=0 | | 9a^2+33a+10=0 | | 10n^2+23n-42=0 | | x+(x+10)=1.10 | | 2(2x-3)+3x=2x+4 | | 10x+6=x(10x+8) | | 2/3-x=9+1/3 | | 5(-1.1707)+6y=30 | | -1+8=7x+8 | | 11a-4a+4=17-a | | 18(2c+5)=3c-20 | | 1.5x+3y=42 | | 93x+1=272x+1 | | 43x-1=64 | | 628=-26+100y | | 628=-26x+100y | | (6s+5p)(6s-5p)= | | 628=-26x+100 | | 8x-1=2x+8 | | y=-2.5x^2+17.5x+161 | | y=-2.5x^2+17.5x+61 | | (x-9)(x-1)+7=0 | | x=x-3-34+57/2+2-3/4 | | 6+9=98 | | x=x-3-34+57 | | x-23=x-3-34+57 | | 5+5s=20 | | 5r-4=40 |

Equations solver categories